CATAGENESIS OF ORGANIC MATTER IN DEEP ZONES OF THE CENTRAL VILYUY SYNECLISE - Syundyukov S.A.; Frolov V.I.; Bakin V.Y. (My University, 1987)
The difficulty and high cost of drilling at depths of more than 5 km makes it necessary to take account of many factors in forecasting the occurrence of oil and gas in deep sedimentary sequences and to check the forecasts by as many methods as are available. One such method is analysis of the degree of alteration of concentrated and dispersed organic matter. The authors conducted such an analysis of organic matter on cores from drillhole SV-27, the deepest in eastern Siberia and the Soviet Far East. It was drilled in order to prospect for oil and gas in the Middle Vilyuy gas and condensate field in the central area of the Vilyuy oil and gas province, on the Khapchagay megaswell. The authors data indicate that a high degree of alteration of organic matter in drillhole SV-27, should be taken into account when revising the forecasts for hydrocarbon reserves in the central Vilyuy Syneclise. Given the extremely small content of alginite material (a fraction of a percent of stratum-average samples or none at all) in both dispersed and concentrated (i.e., coal) organic matter, it is unlikely that any significant oil accumulations will be found there.